SKRINING KETAHANAN BEBERAPA PLASMA NUTFAH UBI JALAR TERHADAP CEKAMAN ALUMINIUM DAN TANAH MASAM - Damayanti, Fitri; Marhento, Giry; A’ini, Zakiyah Fithah; Musliman, Acep (Jurnal Penelitian Pertanian Terapan, 2024)
The increase in demand for sweet potatoes was not accompanied by an increase in production caused by a reduction in the area planted with sweet potatoes due to land conversion from wetlands to marginal lands. However, the available land for the expansion of agricultural areas is dominated by acid soils that are poor in nutrients. The main problem of planting in acid soil is the high content of Aluminum (Al). One of the effective approaches to selecting plants that are resistant to Al is using the solution culture method by adding Al and adjusting the pH of the solution. This activity aimed to obtain and develop the most appropriate and efficient screening method for selecting the resistance of some sweet potato germplasm to Al stress. The plant materials used were several collections of sweet potato germplasm, namely: Antin 1, Antin 3, Beta 1, Beta 2, Kidal, Papua Salosa, Sari, and Sarwentar. The research activities included: (1) Screening of sweet potato shoots in Al solution culture media in the form of AlCl3.6H2O with concentrations of 0, 100, 200, 300, 400, and 500 mg/L with a solution pH of 4.0 and (2) Testing of sweet potato Al tolerant on acid soils, namely yellow red podzolic soil from Bagoang Jasinga Village, Bogor Regency, Indonesia with a pH of 4.4-5.2. The results obtained were two sweet potato varieties that were tolerant of Al and acid soils, namely Kidal and Papua Salosa. Both of these varieties can be used as Al-tolerant and acid-soil-tolerant sweet potato planting material. Meanwhile, Antin was used as a comparison plant material that was intolerant of Al and acid soil.